Judicialização da saúde para o acesso às tecnologias no Sistema Único de Saúde da Bahia, Brasil (2005-2010) - Simões, Aliana Ferreira de Souza (2013)
The health system Ensures the 1988 Constitution, the principles of the Unified Health System (SUS), universality, fairness, integrity cared for in the health of Individuals. Thus, the citizen has the right to life and health legitimized Becoming foundation for the realization of the fundamental right to life, human dignity and citizenship. However, the health system is facing gaps is putting its principles. From this perspective, the lawsuits go into this scenario an instrument for the realization of these rights. The research is Performed to describe the profile of the judicialization of health in the state of Bahia for the access to health technologies in the SUS, in the period from 2005 to 2010, and to discuss access technologies in relation to the demands of health care (drugs, food, admissions, treatments, surgeries and other) and the lawsuits filed by users of SUS. The methodology has two approaches: a quantitative approach, with retrospective descriptive study, from primary sources collected in the database of electronic consultation and free access to the website of the Court of Justice of the State of Bahia, the lawsuits. That demand for access to health technologies in the SUS, in the period from 2005 to 2010. These data comprised the General Headquarters and Analysis Analyzed were using Microsoft Office Excel 2007 for tabulation, build charts and tables for the distribution of absolute and relative frequencies, and the qualitative approach with an exploratory study, descriptive and analytical, using document analysis for the composition Summary Table of the Analysis of Thematic Content Analysis by Defining the Category Analysis. The results obtained by the design of the profile of Legalization of Health in the State of Bahia have 103 lawsuits. That demand for access to technologies in the SUS, in the period from 2005 to 2010. The year 2009 presented significant data entry with 47 stocks (45.6%). 75 actions were recorded (72.8%) Interlocutory Appeal and to the towns of origin, 74 shares (71.8%) were related to the city of Salvador. The drug delivery was more demand pled with 72 (60%). We found 63 cases (61.2%) related to degenerative diseases Chronic and 89, equivalent to 86.4% judgments granting the user access to the SUS. The year 2009 Showed 54 (52.4%) of the cases heard. With the discussion permeated by the Judiciary unveiling a path for access to health technologies in SUS can infer such access that provides the guarantee of the right to life and health to users, because the demands are met pled in almost all the shares. The Civil Society Organizations have great power in the realization of human rights act the key players in the mobilization of the Judiciary for the satisfaction of their rights that have been denied or dissatisfied. For the health system, the demands, especially for drugs by judicial cause great harm to the planning and management of programs and services offered by SUS, and displacement of budget allocations for health to meet the individual lawsuits, the vast Majority. Moreover, there is an excessive medicalization of health care devaluing the relational technologies and the power of the subject active in directing the disease process. Thus, we conclude that traveled this alternative path by the user and allows access to the health system provides citizenship determined by the participation of the individual as a citizen who sections the fulfillment of their social rights established in the Constitution of 1988. However, we envision the need for a strong body of technical professionals in the health field to work together with the Judicial Authorities in the resourcefulness of actions. That require instructions for their acts embrasure decision-making glimpsing consistent and fair to all Involved in the search for a society with social justice.